Emerging applications of nanodiamonds in photocatalysis. Issue 1 (2nd January 2021) - Su, Li-Xia; Cao, Yu; Hao, Hao-Shan; Zhao, Qi; Zhi, Jinfang
Abstract: As a fascinating nanocarbon photocatalytic material, nanodiamonds (NDs) have attracted more and more attention recently due to their high chemical stability, high carrier mobility, narrowing band gap, easy surface modification, and mass production. This review summarizes the latest progress related to elaborated construction of NDs and NDs-based nanocomposite, including microstructure regulation of pristine NDs, elemental doping and formation a heterojunction by coupled with another semiconductor. The construction and properties of each category of NDs-based material are reviewed on their structure, preparation methods, texture control, and photocatalytic performance. Photocatalytic applications of NDs-based nanomaterials for hydrogen evolution from water splitting, organic pollution degradation, CO2 reduction, N2 reduction, graphene oxide reduction, and the latest advances in photocatalytic reaction mechanism have been also systematically reviewed. Finally, the challenges and prospects of the photocatalytic application of NDs are also briefly analyzed.